Hyaluronic acid 0.2 % cream for preventing radiation dermatitis in breast cancer patients treated with postoperative radiotherapy: A randomized, double-blind, placebo-controlled study - Letizia Deantonio; Giulia Borgonovo; Serena Caverzasio; Maria Antonietta Piliero; Paola Canino; Andrea Puliatti; Thomas Zilli; Maria Carla Valli; Antonella Richetti; Antonella Richetti; Maria Carla Valli; Letizia Deantonio; et al. (Breast)
Introduction: This randomized trial evaluated the efficacy and safety of the prophylactic use of a hyaluronic acid (HA) 0.2 %-containing cream to reduce acute radiodermatitis in breast cancer patients undergoing adjuvant radiotherapy (RT). Methods: Candidates for conventionally-fractionated or hypofractionated adjuvant RT for unilateral stage I-III breast cancer were randomized 1:1 to the HA cream or neutral comparator applied twice daily from 14 days before starting until 14 days after completing local RT. The primary endpoint was the development of acute skin dermatitis of grade ≥2 according to RTOG scale at the end of RT. Results: The study closed early after 86 of the planned 120 patients were enrolled because of an unexpectedly low frequency of acute skin toxicity. Cumulative acute grade ≥2 radiodermatitis was lower with the HA cream (21.1 %) than the comparator group (35.3 %) but did not reach statistical significance in the primary endpoint (p = 0.3). At the end of RT, acute dermatitis grade ≥1 occurred in 92 % of patients undergoing conventionally-fractionated RT and 50 % in the hypofractionation subgroup. Physician-based RTOG grading scale and quantitative assessment with skin reflectance spectrophotometry (SRS) measures were comparable in detecting skin toxicity. However, an increase in SRS values was detectable a week before the first signs of radiodermatitis were depicted using RTOG scores. Conclusion: Compared to physician-based grading, SRS enabled earlier detection of skin toxicity and may be used as a valid and effective tool for assessing radiodermatitis. Prophylactic topical HA may help mitigate this toxicity; however adequately powered prospective trials are needed.